2008
DOI: 10.2307/20445490
|View full text |Cite
|
Sign up to set email alerts
|

Pluto Behaving Badly: False Beliefs and Their Consequences

Abstract: We exposed college students to suggestive materials in order to lead them to believe that, as children, they had a negative experience at Disneyland involving the Pluto character. A sizable minority of subjects developed a false belief or memory that Pluto had uncomfortably licked their ear. Suggestions about a positive experience with Pluto led to even greater acceptance of a lovable ear-licking episode. False beliefs and memories had repercussions; those seduced by the bad suggestions were not willing to pay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Typically ‘Believers’ reported an increase on the autobiographical belief scale that ranged from 1 to 2 points, remaining below the scale midpoint, for an event at a theme park (Berkowitz, Laney, Morris, Garry, & Loftus, 2008) to 3–5 points, increasing beyond the scale midpoint, for food‐related events (D. M. Bernstein et al, 2005a, 2005b; Laney et al, 2008; Laney et al, 2008; Scoboria, Mazzoni, Jarry, & Bernstein, 2012). In some cases, belief ratings recorded by ‘Believers’ after false feedback were as high as 6.48 on the 8‐point scale (Laney et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Typically ‘Believers’ reported an increase on the autobiographical belief scale that ranged from 1 to 2 points, remaining below the scale midpoint, for an event at a theme park (Berkowitz, Laney, Morris, Garry, & Loftus, 2008) to 3–5 points, increasing beyond the scale midpoint, for food‐related events (D. M. Bernstein et al, 2005a, 2005b; Laney et al, 2008; Laney et al, 2008; Scoboria, Mazzoni, Jarry, & Bernstein, 2012). In some cases, belief ratings recorded by ‘Believers’ after false feedback were as high as 6.48 on the 8‐point scale (Laney et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Of the studies identifying a subset of ‘Believers’, the proportion endorsing a ‘memory’ as opposed to a ‘belief’ fell between 0% and 20% in studies suggesting the participant had been ill after eating something (D. M. Bernstein et al, 2005a, 2005b) or had had a specific experience at a theme park (Berkowitz et al, 2008). This proportion reached 40% in a study suggesting being sick after drinking alcohol (Clifasefi et al, 2013) and 20–50% in studies involving like or dislike of asparagus (Laney et al, 2008; Laney et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that merely suggesting to people that they experienced a particular event in the past, for example, that they had become ill after eating spoiled peach yogurt, can directly affect how much peach yogurt they consume currently (Scoboria, Mazzoni, & Jarry, 2008). However, other studies have shown that the consequences surrounding suggested food-related events are stronger in those who come to believe the suggestion than in those who do not believe the suggestion (e.g., Berkowitz, Laney, Morris, Garry, & Loftus, 2008). Thus, it is unclear whether suggestions directly affect suggestion-related attitudes and behaviors or whether belief in the suggested events drives changes in suggestionrelated attitudes and behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Other false memory implantation techniques are simpler, designed to give large numbers of subjects false memories quickly (Berkowitz, Laney, Morris, Garry, & Loftus, 2008;Bernstein, Laney, Morris, & Loftus, 2005;Laney, Morris, Bernstein, Wakefield, & Loftus, 2008). An important goal of this research is to root out differences between true and false memories that could be useful to forensic interviewers and other actors in the legal system.…”
Section: False Memorymentioning
confidence: 99%